Perancangan Site Plan Kampung Adat Kuta - Thoriq Ananda Saputra; Astri Mutia Ekasari; Imam Indratno (UPT Publikasi Ilmiah Unisba, 2024)
Abstract. The existence of Kuta Traditional Village in Ciamis Regency is crucial because of the traditional values that must be expressed in the spatial concept, as well as local values and natural conditions. This research aims to develop an architectural design concept that is responsive to local culture and disaster response for the Kuta Traditional Village site plan. The research method involved field surveys, analysis of local cultural conditions, and mapping of disaster risks in the area. A participatory approach with local communities and stakeholders was also applied to understand the needs and aspirations of the community. The research results are expected to produce a site plan design guide framework that combines local cultural values with disaster response infrastructure. The design includes multifunctional public open spaces, integration of vernacular architecture with modern environmentally friendly technology, and land use planning that takes into account disaster risk mitigation such as earthquakes and fires. This research is expected to make a significant contribution to the practice of designing cultural architecture that is responsive to the challenges of natural disasters, as well as a reference for the development of a sustainable Kampung Adat Kuta area that strengthens local cultural identity while being able to mitigate disaster risks. Abstrak. KKeberadaan Kampung Adat Kuta di Kabupaten Ciamis krusial karena nilai adat yang harus dituangkan dalam konsep tata ruang, serta nilai lokal dan kondisi alamnya. Penelitian ini bertujuan mengembangkan konsep perancangan arsitektur yang responsif terhadap budaya lokal dan tanggap bencana untuk site plan Kampung Adat Kuta. Metode penelitian melibatkan survei lapangan, analisis kondisi budaya lokal, serta pemetaan risiko bencana di kawasan tersebut. Pendekatan partisipatif dengan komunitas setempat dan pemangku kepentingan juga diterapkan untuk memahami kebutuhan dan aspirasi masyarakat. Hasil penelitian diharapkan menghasilkan kerangka panduan perancangan site plan yang menggabungkan nilai-nilai budaya lokal dengan infrastruktur tanggap bencana. Desain mencakup ruang terbuka publik multifungsi, integrasi arsitektur vernakular dengan teknologi modern yang ramah lingkungan, serta perencanaan tata guna lahan yang memperhatikan mitigasi risiko bencana seperti gempa bumi dan kebakaran. Penelitian ini diharapkan memberikan kontribusi signifikan dalam praktek perancangan arsitektur budaya yang responsif terhadap tantangan bencana alam, serta menjadi acuan bagi pengembangan kawasan Kampung Adat Kuta yang berkelanjutan dan memperkuat identitas budaya lokal sambil mampu menanggulangi risiko bencana.